2022
DOI: 10.1007/s13555-022-00806-x
|View full text |Cite
|
Sign up to set email alerts
|

Body Site Distribution of Acquired Melanocytic Naevi and Associated Characteristics in the General Population of Caucasian Adults: A Scoping Review

Abstract: The number of melanocytic naevi is a major risk factor for melanoma. The divergent pathway hypothesis proposes that the propensity for naevus proliferation and malignant transformation may differ by body site and exposure to ultraviolet (UV) radiation. This scoping review aimed to summarise the evidence on the number and distribution of naevi (C 2 mm) on the body overall and by individual anatomical sites in Caucasian adults, and to assess whether studies used the International Agency for Research on Cancer (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
(199 reference statements)
1
1
1
Order By: Relevance
“…Again, this difference could be explained by the older study cohort and the fact that the number of lentigines significantly increases with age [18]. Jayasinghe et al [30] reported that males had the highest nevus counts on the trunk, as opposed to our findings (both men and women revealed multiple common nevi most frequently on the lower extremities). We considered both the entire thighs and lower legs as lower extremities, which might account for the greater nevus counts on this body area compared to the trunk.…”
Section: Discussioncontrasting
confidence: 91%
“…Again, this difference could be explained by the older study cohort and the fact that the number of lentigines significantly increases with age [18]. Jayasinghe et al [30] reported that males had the highest nevus counts on the trunk, as opposed to our findings (both men and women revealed multiple common nevi most frequently on the lower extremities). We considered both the entire thighs and lower legs as lower extremities, which might account for the greater nevus counts on this body area compared to the trunk.…”
Section: Discussioncontrasting
confidence: 91%
“…This is consistent with the findings of a recent comprehensive review of the biology and genetics of MN that concluded that their anatomical distribution and signature mutations support the existence of UVR-related and non-UVR pathways in the development of MN [ 38 ]. Similar conclusions have been reached by dermoscopic [ 18 ] and epidemiological studies [ 39 , 40 , 41 ] that compared MN by age, anatomical site, and inferred pattern of sun exposure. It is anticipated that future research that increases our understanding of nevogenesis and the natural history of MN will further elucidate the biological pathways to melanoma development, but this remains a work in progress [ 38 , 42 , 43 , 44 ].…”
Section: Introductionsupporting
confidence: 80%
“…However, MN frequency is similar in older individuals from these contrasting climates, suggesting that early acquisition of MN increases melanoma risk [ 16 , 30 , 45 ]. Because sun exposure is related to MN development during childhood [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 32 , 35 , 36 ], and MN count and sun exposure are both risk factors for cutaneous melanoma [ 3 , 4 , 5 , 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 24 , 32 , 39 , 40 , 43 , 45 ], MN counts provide a short-term measure of the efficacy of interventions designed to reduce sun exposure and subsequent melanoma risk [ 46 , 47 , 48 ]. Australia is recognized internationally for its skin cancer prevention programs dating back to the 1980s [ 7 ]; thus, when our randomized controlled trial (RCT) commenced, most (97.8 percent) accredited childcare centers in Queensland already had a written sun protection policy requiring children to use high sun protection factor (SPF) sunscreen and wear a hat at childcare [ 49 ], while protective clothing was underutilized [ 46 ].…”
Section: Introductionmentioning
confidence: 99%